If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 336 = 7(7n + 6) Reorder the terms: 336 = 7(6 + 7n) 336 = (6 * 7 + 7n * 7) 336 = (42 + 49n) Solving 336 = 42 + 49n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-49n' to each side of the equation. 336 + -49n = 42 + 49n + -49n Combine like terms: 49n + -49n = 0 336 + -49n = 42 + 0 336 + -49n = 42 Add '-336' to each side of the equation. 336 + -336 + -49n = 42 + -336 Combine like terms: 336 + -336 = 0 0 + -49n = 42 + -336 -49n = 42 + -336 Combine like terms: 42 + -336 = -294 -49n = -294 Divide each side by '-49'. n = 6 Simplifying n = 6
| (-4)(-4)(-4)=y | | 4x-7=2x-14 | | Onehalf+2= | | -3u=12 | | 3(-6y+7)+4y=-7 | | 4-(3b-8)=2b-17 | | -7=5-4r+7r | | 6y^2-54= | | 2=9x-3 | | X+2x=5x-10 | | 7c-6-9c=3 | | -2(4-r)-5=11 | | 2x^2-15+7=0 | | 4n+0=4n | | -6x(-7)=y | | 5u^2+13u-6= | | 4x+12=12x-42 | | 3x-3+4x-3= | | x-0.10x=126 | | -24-(-28)=y | | 7m-3m=12 | | 2x-12+3x-7=6x-31 | | 625+(2-5)= | | 3x-7y=z | | 9-(-8)=y | | 2a^2-23=0 | | -4(3q+5)=-16 | | 5-(-7)=y | | 3x-3+4x-3-(1-x)= | | (1+x)(1+x)=1+6x | | 3x-6+2x+6=45 | | -16t^2+80t-64=0 |